Take the 2-minute tour ×
MathOverflow is a question and answer site for professional mathematicians. It's 100% free, no registration required.

What are the general solutions of the functional equations?

$$ f(x,y)+f(y,z)=\frac{1}{f(x,z)} $$

$$ f(x,y)f(y,z)f(x,z)=1 $$

share|improve this question
1  
Putting $x=y=z$, you get $2X^2=1$, and $X^3=1$ where $X=f(x,x)$, which is nonsense. –  i707107 May 8 '13 at 14:12
    
Or, are those separate problems? –  i707107 May 8 '13 at 14:13
    
The functional equations are independent, it's not a system of equations. –  Umar May 8 '13 at 14:21
    
You can expand in power series around the $x=y=z$ locus, setting $y = x + \epsilon$ and $z = x + \delta$. This at least gives you formal solutions. –  S. Carnahan May 8 '13 at 14:44
3  
The question would be more interesting if we knew what motivates it... –  Qfwfq May 8 '13 at 19:10
show 2 more comments

2 Answers 2

You don't need to assume any differentiability (or even continuity). In fact, the domain of $f$ need have no structure other than being a set of the form $D\times D$ for some other set $D$.

I'll assume that the range of $f$ in each case is $\mathbb{R}$, even though the OP didn't specify that. I suppose that, more generally, for the first equation, $f$ could take values in any field $\mathbb{F}$ (or even a division ring), and the answer might differ a little bit in that case, depending on the nature of $\mathbb{F}$. For the second equation, perhaps one could allow $f$ to take values in a group $\mathbb{G}$ to get a more general problem.

For the first equation, setting $x=y=z$, one sees that $f(x,x)=\epsilon(x)/\sqrt{2}$ for some function $\epsilon$ that satisfies $\epsilon(x)=\pm 1$. However, now, setting $z=x$, one has $f(x,y)+f(y,x)=\sqrt{2}\epsilon(x)=\sqrt{2}\epsilon(y)$ for all $x$ and $y$, so $\epsilon$ is constant. Replacing $f$ by $-f$ if necessary, one can assume $\epsilon(x)\equiv1$, so that $f(x,y)+f(y,x)\equiv\sqrt{2}$. Thus, set $f(x,y) = 1/\sqrt{2}+a(x,y)$ where $a(x,y)=-a(y,x)$. Substituting this back into the equation with $x=y$ yields $\sqrt{2}+a(x,z)=1/\bigl(1/\sqrt{2}+a(x,z)\bigr)$, which gives $a(x,z)\bigl(a(x,z)+3/\sqrt{2}\bigr)=0$. Thus, either $a(x,z)=0$ or $a(x,z)=-3/\sqrt{2}$. However, the latter is not possible since then $a(z,x)=3/\sqrt{2}$, which is not allowed. Thus, $a(x,z)=0$ for all $x$ and $z$. Thus, $f(x,y)\equiv1/\sqrt{2}$ and $f(x,y)\equiv -1/\sqrt{2}$ are the only solutions.

Similarly, for the second equation, one has $f(x,x)^3=1$, so $f(x,x)=1$. Setting $z=x$, yields $f(x,y)f(y,x)=1$, so $f(x,y)=1/f(y,x)$ for all $x$ and $y$. Suppose that there is a pair $(x,y)$ such that $f(x,y) < 0$. Then for any $z$, one has $f(x,z)f(y,z) < 0$, so either $f(x,z) < 0$ or $f(y,z) < 0$ (and not both). Let $Y$ be the set of $z$ such that $f(x,z) < 0$ and let $X$ be the set of $z$ such that $f(y,z) < 0$. Then $X$ and $Y$ are disjoint and nonempty and their union is everything. If $z$ and $w$ belong to $Y$, then the equation $f(x,z)f(z,w)f(x,w)=1$ implies $f(z,w)>0$. Similarly, if $z$ and $w$ belong to $X$, then $f(z,w)>0$.

Letting $\epsilon(z,w)=1$ when $f(z,w)>0$ and $\epsilon(z,w)=-1$ when $f(z,w)<0$, the function $g$ defined by $g(z,w)=f(z,w)\epsilon(z,w)=|f(z,w)|$ will satisfy the same functional equation as $f$ but will be positive everywhere. Writing $h(z,w)=\log\bigl(g(z,w)\bigr)$, one sees that $h$ satisfies the functional equation $$ h(u,v) + h(v,w) + h(u,w)=0 $$ But this says that $h(v,w)=-h(u,v)-h(u,w)=h(w,v)$, while one already knows that $h(v,w)=-h(w,v)$. Thus $h(v,w)\equiv0$, so $g(v,w)\equiv1$.

Thus, the solutions of the second functional equation are obtained as follows: Write the domain $D$ as a disjoint union of two sets $X$ and $Y$ and set $f(z,w) = +1$ when $z$ and $w$ both belong to either $X$ or $Y$ and $f(z,w)=-1$ otherwise.

share|improve this answer
add comment

If you assume smoothness of f, both identities lead to f being constant. For the first one, take the derivative with respect to x and y. You find $$f_{xy}=0.$$ Now take the derivative with respect to x and z. This yields zero on the left, and on the right, since you already know $$f_{xz}=0,$$ you find $$f_z=0.$$ So we have $$f(x,y)=a(x)+b(y)$$ with b'=0, and f is constant.

For the second problem, let $$g=\ln f,$$ and you find $$g(x,y)+g(y,z)+g(x,z)=0.$$ Again you find $$g_{xy}=0,$$ so $$g(x,y)=a(x)+b(y),$$ and $$2a(x)+a(y)+b(y)+2b(z)=0.$$ Taking derivatives with respect to x and z, we find that a and b must be constant.

share|improve this answer
1  
Your notation is a bit confusing when dealing with a functional equation, you should use indices $1$ and $2$ for the derivatives rather than variable names. –  Benoît Kloeckner May 8 '13 at 15:26
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.